EFEKTIVITAS KARBON AKTIF BONGGOL JAGUNG (ZEA MAYS) UNTUK MENURUNKAN KADAR BESI (FE) AIR SUMUR GALI DI KELURAHAN PADANG SERAI KOTA BENGKULU - yusmidiarti; Juniarta Simangunsong, Yesika (Jurnal Sanitasi Profesional Indonesia, 2021)
Water is one of the natural resources that has a very important function for human life where there is not a single living creature on this earth that does not need water. The results of examination of dug well water samples for iron (Fe) levels were 2.17 mg / L. The type of research to be conducted is a semi-experiment, with a pretest posttest design research design (Sugiono, 2017). Primary data obtained by researchers through observation and measurement of iron content (Fe) from the dug wells of residents in RT 08, Padang Serai, before the administration of corn cobs active charcoal and after the administration of corn cobs active charcoal. It can be seen that the pre-test on Iron (Fe) is 2.17 mg / L. The average value of active carbon reduction at a thickness of 15 cm is 51%. average thickness of 20 cm is 51%, and thickness of 25 cm is on average 56%. With the results of this study can enrich library references and increase knowledge and provide information about the use of active karbo corncobs.